Coastal area rehabilitation for climate change adaptation: The key role of mangroves in Nationally Determined Contributions - Jompa, J.; Murdiyarso, D. (CIFOR-ICRAF, 2023)
With a coastline of more than 90,000 km – the second longest after Canada – it is in Indonesia’s interests to protect its coastal areas from climate change impacts. The continued existence and preservation of extensive coastal vegetation like mangroves and seagrasses is a nature-based solution for successful adaptation to climate change. A coastal area rehabilitation/restoration agenda for climate change adaptation must be able to increase areas’ resilience in overcoming rising sea levels, waves, coastal erosion, flooding and inundation, so the resilience of communities, particularly fishing communities living in coastal areas, can be enhanced. Communities’ social cohesion, economic opportunities, and institutional capacity must also improve. Information and funding flows must be transparent for all stakeholders, so adaptation agenda decision making and implementation can be carried out effectively, efficiently and equitably.